Comparison of Ultrafast Papanicolaou stain with standard Papanicolaou stain for cervical smear - Pudasaini, Sujata; Pathak, Rakesh; Pande, Kricha; Koirala, Shraddha (Journal of Pathology of Nepal, 2018)
Background: After the first evolution of Papanicolaou smear, it has been successfully used to screen cervical cancer. With modifications in the staining method of Pap stain, the lesser staining time and unequivocal cell morphology has been achieved by Ultrafast Papanicolaou stain. The aim of this study is to compare the UFP stain and SP stain in cervical pap smears on the basis of background, cell morphology, nuclear details and overall staining. Materials and methods: This is a prospective hospital based study conducted in a tertiary hospital, Nepal Medical College over a period of six months (January 2017 to June 2017). Cervical pap smears received in the department of Pathology is subjected to Standard papanicolaou (SP) stain and Ultrafast papanicolaou (UFP) stain for comparison. Results: Total of 368 cervical pap smears were subjected to SP stain and UFP stain. Mean age of the patient was 36.57+-10.06 years. The quality of UFP stain was assessed by considering the background, cell morphology, nuclear details and overall staining. Difference in regards to the interpretation and background was not significant when SP stain was compared to UFP stain. However, cell morphology, nuclear details and overall staining were far better in smears stained with UFP stain. Conclusion: Pap smear is the simple and effective screening tool for cervical lesions. With modifications in staining method and introduction of UFP stain, the result is lesser staining time and excellent morphological quality. Hence, UFP stain has become the choice of stain and can be used on a regular basis.